2010
DOI: 10.1021/ie100530p
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of α-Olefin Copolymerization with Chain-Shuttling Chemistry Using Dual Catalysts in Stirred-Tank Reactors: Molecular Weight Distributions and Copolymer Composition

Abstract: We report a kinetic model of chain-shuttling copolymerization using dual catalysts for solution α-olefin polymerization processes. This model focuses on predicting polymer properties such as the molecular weight and molecular weight distribution and the overall copolymer composition. We first validate the model through qualitative comparison between the model predictions and experimental observations reported in Arriola et al. (Science) in both a semibatch reactor and a continuous stirred-tank reactor (CSTR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(73 citation statements)
references
References 50 publications
3
70
0
Order By: Relevance
“…We selected these values from the literature for ethylene/1-octene chain-shuttling polymerization using dual catalysts. [12] The initial number of ethylene molecules is 1 × 10 9 and the ethylene concentration is 2.63 mol L −1 ; the concentrations of the other reactants were calculated based on this information. The total polymerization time was 600 s for the targeted M n ≈ 54 000 g mol −1 .…”
Section:  → +mentioning
confidence: 99%
See 1 more Smart Citation
“…We selected these values from the literature for ethylene/1-octene chain-shuttling polymerization using dual catalysts. [12] The initial number of ethylene molecules is 1 × 10 9 and the ethylene concentration is 2.63 mol L −1 ; the concentrations of the other reactants were calculated based on this information. The total polymerization time was 600 s for the targeted M n ≈ 54 000 g mol −1 .…”
Section:  → +mentioning
confidence: 99%
“…Models for chain-shuttling polymerization in continuous stirred-tank reactors (CSTRs) were first developed using the method of moments to describe polymerization kinetics and average chain microstructures. [12,13] Because this approach cannot generate detailed microstructural distributions, Monte Carlo (MC) models were later developed for OBCs made in CSTRs operated at steadystate. [14][15][16] Subsequently, Mohammadi et al developed Chain-shuttling polymerization with dual catalysts has introduced a new class of polyolefins called olefin block copolymers (OBCs).…”
mentioning
confidence: 99%
“…Modeling studies reported so far were devoted to the analysis of copolymer composition, molecular weight distribution, length of the blocks, distribution of the number of blocks per chain and to finer microstructure analysis and its evolution during the polymerization . It has notably been shown that the Mayo − Lewis equation may no longer be able to describe the composition of the copolymers formed instantaneously by each catalyst in CSP systems operating in a continuous stirred tank reactor (CSTR) .…”
Section: Theoretical Modeling Of Cspmentioning
confidence: 99%
“…The influence of the relative amount of catalyst in the reactive medium also shows some particular effects . Considering the system developed by Dow Chemical, the Hf based catalyst 2 inserts more 1‐octene in the copolymer than 1 .…”
Section: Theoretical Modeling Of Cspmentioning
confidence: 99%
“…In an earlier publication, Zhang et al also report a theoretical analysis on the copolymer composition for chain shuttling copolymerization and pointed out that the Mayo–Lewis equation could potentially be invalid for dual catalysts. Yet in another publication, Zhang used a kinetic model of chain‐shuttling copolymerization for dual catalysts in solution polymerization processes to predict molecular weight, molecular weight distribution, and the overall copolymer composition. The model was validated against earlier publications and, subsequently, used to examine the effects of the chain‐shuttling rate constant and the chain shuttling agent feed rate in a CSTR as well as to prepare polymers with desired properties by manipulating catalyst compositions and monomer compositions in the feed.…”
Section: Introductionmentioning
confidence: 99%